2D Porous TiO2 Single‐Crystalline Nanostructure Demonstrating High Photo‐Electrochemical Water Splitting Performance. Issue 21 (14th May 2018) - Butburee, Teera; Bai, Yang; Wang, Huanjun; Chen, Hongjun; Wang, Zhiliang; Liu, Gang; Zou, Jin; Khemthong, Pongtanawat; Lu, Gao Qing Max; Wang, Lianzhou
Abstract: Porous single crystals are promising candidates for solar fuel production owing to their long range charge diffusion length, structural coherence, and sufficient reactive sites. Here, a simple template‐free method of growing a selectively branched, 2D anatase TiO2 porous single crystalline nanostructure (PSN) on fluorine‐doped tin oxide substrate is demonstrated. An innovative ion exchange–induced pore‐forming process is designed to successfully create high porosity in the single‐crystalline nanostructure with retention of excellent charge mobility and no detriment to crystal structure. PSN TiO2 film delivers a photocurrent of 1.02 mA cm −2 at a very low potential of 0.4 V versus reversible hydrogen electrode (RHE) for photo‐electrochemical water splitting, closing to the theoretical value of TiO2 (1.12 mA cm −2 ). Moreover, the current–potential curve featuring a small potential window from 0.1 to 0.4 V versus RHE under one‐sun illumination has a near‐ideal shape predicted by the Gartner Model, revealing that the charge separation and surface reaction on the PSN TiO2 photoanode are very efficient. The photo‐electrochemical water splitting performance of the films indicates that the ion exchange–assisted synthesis strategy is effective in creating large surface area and single‐crystalline porous photoelectrodes for efficient solar energy conversion. Abstract : A new strategy is developed to create high porosity and abundant reactive sites on TiO2 single‐crystalline nanostructures with retention of excellent charge mobility and no detriment to crystal structure. The novel porous single‐crystalline nanostructured film delivers excellent photo‐electrochemical performance, which sheds light on the design of high‐performing nanostructured materials.